Sociolinguistic variations of Spanish in Peru - Godenzzi, Juan Carlos (1987)
Nine years have passed since the publication of this book and, nevertheless, it seems appropriate to review it because perhaps it has not been sufficiently valued. In the first chapter, Escobar presents us with the working premises that will serve as a starting point.